Physicochemical properties of pomelo (Citrus grandis L. Osbeck) byproducts - Abd Rahman, Nur Farhana; Shamsudin, Rosnah; Ismail, Amin; Abdul Karim Shah, Nor Nadiah; Varith, Jaturapatr (Malaysian Society of Agricultural Engineers, 2019)
Pomelo (Citrus grandis L. Osbeck) is known as the largest citrus fruit in the worlds. The fresh pulp often consumed directly meanwhile pomelo byproducts including peels; exocarp: flavedo and endocarp: albedo and lamella were discarded. A significant yield of waste was produced and may result in high cost of waste management. Therefore, the present study was carried out after freeze-drying (FD) to discover the physico-chemical properties (water activity (aw), total soluble solids (TSS), pH and vitamin C) of pomelo byproducts (flavedo, albedo and lamella). Results showed that the overall byproducts contain lower water activity (<0.7) value after dried, whereas for TSS albedo (2.43°Brix) and lamella (2.23°Brix) showed significantly (p <0.05) higher value compared to flavedo (1.77°Brix). Similar with pH analysis, significant lower value of flavedo (5.44) was observed in comparison with albedo (5.78) and lamella (5.70). Nevertheless, lower pH value indicates the presence of higher concentration of vitamin C in flavedo (30.52 mg AA/100g DW) more than albedo (25.83 mg AA/100g DW) and lamella (17.48 mg AA/100g DW). Noteworthy information of the byproducts could be further applied in nutraceutical approach and functional foods for commercial purposes.